2022
DOI: 10.1007/s11575-022-00490-1
|View full text |Cite
|
Sign up to set email alerts
|

E-commerce Policy and the Global Economy: A Path to More Inclusive Development?

Abstract: The advancement of digitalization is gradually transforming the existing structure of the global economy. According to the McKinsey Global Institute, almost all cross-border transactions had a digital component in 2016. This is also reflected by the growing literature on digitalization and E-commerce. Yet, studies specifically focusing on E-commerce policy are scarce compared with other areas in this domain. By going beyond academic articles and including policy documents in our analysis, this study takes stoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 98 publications
0
7
0
3
Order By: Relevance
“…Ahora bien, estos cambios financieros no sólo le han sucedido la sociedad peruana sino también la gran mayoría de países latinoamericanos, los cuales están teniendo diversas divergencias en el área financiera, puesto que por más que cuenten con una regulación interna está no se da abasto a las múltiples transacciones dinerarias que suceden en sus estados en otras palabras no logran regular todas las transferencias pecuniarias que se realizan de manera simultánea (López, Condon, & Muñoz, 2021). De igual manera, es importante que todo país tenga normativas que estén siempre a la ayuda de su sociedad, puesto que las diferentes modalidades de emprendimiento por parte de los ciudadanos dan pie a que se realice también nuevas formas delictivas, ya que si no se controla es probable que la economía de un estado quede en un quiebre económico por falta de apoyo (Ahi, Sinkovics, & Sinkovics, 2023). Por otro lado, cabe indicar que nuestra sociedad financiera ante la amenaza de este tipo de transacciones virtuales, los cuales están dentro de la esfera bancaria de nuestro país, por lo que se encuentra regulado en la normativa DL29985 cuyo art.…”
Section: Resultsunclassified
“…Ahora bien, estos cambios financieros no sólo le han sucedido la sociedad peruana sino también la gran mayoría de países latinoamericanos, los cuales están teniendo diversas divergencias en el área financiera, puesto que por más que cuenten con una regulación interna está no se da abasto a las múltiples transacciones dinerarias que suceden en sus estados en otras palabras no logran regular todas las transferencias pecuniarias que se realizan de manera simultánea (López, Condon, & Muñoz, 2021). De igual manera, es importante que todo país tenga normativas que estén siempre a la ayuda de su sociedad, puesto que las diferentes modalidades de emprendimiento por parte de los ciudadanos dan pie a que se realice también nuevas formas delictivas, ya que si no se controla es probable que la economía de un estado quede en un quiebre económico por falta de apoyo (Ahi, Sinkovics, & Sinkovics, 2023). Por otro lado, cabe indicar que nuestra sociedad financiera ante la amenaza de este tipo de transacciones virtuales, los cuales están dentro de la esfera bancaria de nuestro país, por lo que se encuentra regulado en la normativa DL29985 cuyo art.…”
Section: Resultsunclassified
“…As indicated by A. Ahi, N. Sinkovics, & R. Sinkovics (2023), the opportunities of e-commerce represent potential business advantages, transforming the entrepreneurial landscape overall and necessitating support for these changes through the appropriate legal framework.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A noteworthy statistic from the U.S. Census Bureau revealed that, as of the second quarter of 2021, e-commerce constituted approximately 14.3% of total retail sales in the United States, underscoring its growing significance in the retail sector. In China, the prevalence of online retail dominance is even more pronounced, with e-commerce accounting for about 34.7% of total retail sales in 2020 [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%